A Study into the Impact of Entrepreneurial Marketing in the UK Design Industry - Bahaya Alvarez, Omar (2012)
The aim of this study is to explore how Entrepreneurial Marketing can help design consultancies add value, remain competitive and ultimately survive and thrive in challenging times.